1981
DOI: 10.1530/jrf.0.0610325
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of arachidonic acid and other fatty acids in the lipids of guinea-pig uterus and plasma in relation to uterine prostaglandin synthesis

Abstract: Summary. Prostaglandin precursor fatty acids, predominantly arachidonic acid, were found in the different lipid classes of guinea-pig uterus and plasma on Days 7 and 15 of the oestrous cycle. Of the total arachidonic acid in the uterus, 93% was esterified to uterine phospholipids, of which 80% was bound to phosphatidylcholine and phosphatidylethanolamine. There was a significant decrease in the quantity of arachidonic acid bound to phosphatidylcholine between Days 7 and 15 of the oestrous cycle. Less than 0\m=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Presumably Ca2+ combines with calmodulin, which in turn combines with PLA-2 and thereby activates the enzyme to release arachidonic acid for PG synthesis from phospholipids. The main phospholipids involved appear to be phosphatidylcholine and phosphatidylethanolamine (Leaver & Poyser, 1981;Ning & Poyser, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably Ca2+ combines with calmodulin, which in turn combines with PLA-2 and thereby activates the enzyme to release arachidonic acid for PG synthesis from phospholipids. The main phospholipids involved appear to be phosphatidylcholine and phosphatidylethanolamine (Leaver & Poyser, 1981;Ning & Poyser, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, the calcium ionophore causes an influx of Ca2 + into the uterine cells which in turn stimulates PLA-2 to release arachidonic acid from phospholipids (the major source of arachidonic acid in the guinea-pig uterus; Leaver & Poyser, 1981) for PG synthesis. TMB-8 (150 µ ) completely abolished this stimulatory effect of A23187 on uterine output from the Day-15 guinea-pig uterus indicating that, at this concentration, TMB-8 is able to antagonize fully the effects of a rise in the intracellular free Ca2+ concentration in the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma lipids are not the only source of fatty acids for endometrial lipids, as suggested by the relative enrichment in polyunsaturated fatty acids (e.g. arachidonic) in uterine lipids as com¬ pared to blood (Leaver & Poyser, 1981) and by the fact that human endometrium actively incorpo¬ rates [ 1 -' 4C]acetate into polar and neutral glycerolipids (Merrill & Werthessen, 1966). The presence of 22 carbon tetra-, penta-, and hexa-enoic fatty acids suggests that elongating enzymes and desaturases are operative in endometrial tissue since these fatty acids are in exceedingly low concen¬ trations in plasma lipids.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatidyl-choline and -ethanolamine contribute almost equally to the total arachidonate in endometrium, since although the percentage of arachidonate is twice as low in phosphatidylcholine than in phosphatidylethanolamine, the content of the former is double that of the latter. As in the guinea-pig uterus (Leaver & Poyser, 1981 (Thorburn & Challis, 1979) and prostaglandin synthetase has been detected in various subcellular fractions of endometrium (Wlodawer, Kindahl & Hamberg, 1976). The release of arachidonic and eicosatrienoic acids from endometrial glycerophospholipids is a prerequisite for prostaglandin formation.…”
Section: Resultsmentioning
confidence: 99%